Ichthyosis Prematurity Syndrome: A Rare Form but Easily Recognizable Ichthyosis - Sultan Al-Khenaizan; Asma AlSwailem; Mohammed Ali AlBalwi (Karger Publishers, 2021)
Ichthyosis prematurity syndrome is a rare autosomal recessive genodermatosis that is associated with mutations in the SLC27A4 gene. Its onset occurs in early childhood and presents with the clinical triad of premature birth, thick caseous desquamating epidermis, and neonatal asphyxia. Here, we describe a prematurely born baby patient (33 weeks of gestation) with a homozygous variant at the initiation codon site (c.1 A> G, p.Met1Val) in the SLC27A4 gene to raise awareness of this rare syndrome despite its distinctive features as we believe it is still underdiagnosed.